2020
DOI: 10.3390/v12010125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Immune Response of MERS-CoV Vaccine Candidates Derived from Two Different Vectors in Mice

Abstract: Middle East respiratory syndrome (MERS) is an acute, high-mortality-rate, severe infectious disease caused by an emerging MERS coronavirus (MERS-CoV) that causes severe respiratory diseases. The continuous spread and great pandemic potential of MERS-CoV make it necessarily important to develop effective vaccines. We previously demonstrated that the application of Gram-positive enhancer matrix (GEM) particles as a bacterial vector displaying the MERS-CoV receptor-binding domain (RBD) is a very promising MERS va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…The majority of the treatment options and strategies that are being evaluated for SARS-CoV-2 (COVID-19) have been taken from our previous experiences in treating SARS-CoV, MERS-CoV, and other emerging viral diseases. Several therapeutic and preventive strategies, including vaccines, immunotherapeutics, and antiviral drugs, have been exploited against the previous CoV outbreaks (SARS-CoV and MERS-CoV) ( 8 , 104 , 164 167 ). These valuable options have already been evaluated for their potency, efficacy, and safety, along with several other types of current research that will fuel our search for ideal therapeutic agents against COVID-19 ( 7 , 9 , 19 , 21 , 36 ).…”
Section: Vaccines Therapeutics and Drugsmentioning
confidence: 99%
“…The majority of the treatment options and strategies that are being evaluated for SARS-CoV-2 (COVID-19) have been taken from our previous experiences in treating SARS-CoV, MERS-CoV, and other emerging viral diseases. Several therapeutic and preventive strategies, including vaccines, immunotherapeutics, and antiviral drugs, have been exploited against the previous CoV outbreaks (SARS-CoV and MERS-CoV) ( 8 , 104 , 164 167 ). These valuable options have already been evaluated for their potency, efficacy, and safety, along with several other types of current research that will fuel our search for ideal therapeutic agents against COVID-19 ( 7 , 9 , 19 , 21 , 36 ).…”
Section: Vaccines Therapeutics and Drugsmentioning
confidence: 99%
“…The immune responses to these vaccine candidates were evaluated in BALB/c mice for cellular and humoral immune responses, which showed that RVbased vaccine stimulates significantly higher levels of cellular immunity and earlier antibody responses in comparison to the GEM particle vector. 12 The possibility of developing a universal CoV vaccine was assessed based on the similarity in T-cell epitopes of SARSand MERS-CoV that confirmed the potential for crossreactivity among CoVs. 25 SARS-CoV-2 shares high genetic similarity with the SARS-CoV 26 such that vaccines developed for SARS-CoV may exhibit cross-reactivity to SARS-CoV-2.…”
Section: Vaccinesmentioning
confidence: 99%
“…5 Various vaccines, immunotherapeutics, and drug options have been explored during the recent threats of Zika, Ebola, and Nipah viruses [6][7][8] as well as against previous CoVs including SARS-and MERS-CoVs. 3,5,[9][10][11][12] These valuable options can be exploited for their potency, efficacy, and safety along with expediting other ongoing research 2,4,[13][14][15] so as to discover valuable modalities for tackling the emerging COVID-19, but as yet there is no effective vaccine or therapeutic, for which intense efforts are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the therapeutic options and strategies that we are evaluating in SARS-CoV-2 (COVID-19) are taken from our previous experiences in treating SARS-CoV, MERS-CoV, and other emerging viral diseases. Several therapeutic and preventive strategies, including vaccines, immunotherapeutics, and antiviral drugs, have been explored against the previous coronavirus outbreaks caused by SARS-CoV and MERS-CoV (8,104,(164)(165)(166)(167). These valuable options have already been evaluated for their potency, efficacy, and safety along with several other ongoing types of research will fuel our search for ideal therapeutic agent against COVID-19 (7,9,19,21,36).…”
Section: Vaccines Therapeutics and Drugsmentioning
confidence: 99%
“…The RV vector-based vaccines against MERS-CoV can induce faster antibody response as well as higher degrees of cellular immunity compared to the Gram-positive enhancer matrix (GEM) particles vector-based vaccine. However, the latter can induce a very higher antibody response at lower doses (167). Hence, the degree of humoral and cellular immune response produced by such vaccines depends upon the vector used.…”
Section: Vaccinesmentioning
confidence: 99%